2011
DOI: 10.1002/lary.21430
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for auditory neuropathy spectrum disorder in NICU infants compared to normal‐hearing NICU controls

Abstract: In high-risk NICU infants IRDS, meningitis and vancomycin administration are associated with auditory neuropathy spectrum disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
(32 reference statements)
3
15
0
2
Order By: Relevance
“…We suspect that an interference of initial auditory maturation and later auditory neuropathy plays a role. This child meets the criteria that are essential for auditory neuropathy, namely recordable otoacoustic emissions (normal functioning cochlea) and absent or atypical ABR (abnormal transduction from the inner hair cell to the brainstem) . Furthermore, this case illustrates the importance of long‐term follow‐up even when normal hearing levels have been reached.…”
Section: Discussionmentioning
confidence: 79%
“…We suspect that an interference of initial auditory maturation and later auditory neuropathy plays a role. This child meets the criteria that are essential for auditory neuropathy, namely recordable otoacoustic emissions (normal functioning cochlea) and absent or atypical ABR (abnormal transduction from the inner hair cell to the brainstem) . Furthermore, this case illustrates the importance of long‐term follow‐up even when normal hearing levels have been reached.…”
Section: Discussionmentioning
confidence: 79%
“…In a vast majority of infants even born at 26 weeks of gestation, an auditory signal could be detected in the developing brain (Coenraad et al 2011b). Also, differences in aetiologic factors could be seen distinguishing between infants with certain diseases and without these diseases (Coenraad et al 2011a). These outcomes are promising and suggest that indeed ABR can be used to quantify infants' hearing.…”
Section: Sound Designmentioning
confidence: 99%
“…The Joint Committee on Infant Hearing (JCIH) published the risk factors for infant hearing, such as aspiration syndrome, asphyxia, hyperbilinubinemia, low birth weight, sepsis, and ototoxic medication [14]. Many authors have studied the presence of risk factors identified by the JCIH [15-17]. However, little attention is placed on these etiologic factors-associated pathophysiological dysfunctions and hearing outcomes of these pathophysiological dysfunctions.…”
Section: Introductionmentioning
confidence: 99%